Electrocardiogram abnormalities and CVD mortality: prospective cohort study of Tehran lipid and glucose study - Soma Mahmoodian; Davood Khalili; Fereidoun Azizi; Noushin Haddizadeh; Bijan Nouri; Abbas Aghaei (BMC Public Health, 2025)
Abstract Background The incorporation of electrocardiogram (ECG) abnormalities with other clinical indicators can strengthen the hypothesis regarding the improvement of diagnosis and the enhancement of screening accuracy for cardiovascular diseases. This study aimed to determine the risk of mortality from cardiovascular diseases (CVD) based on ECG abnormalities, in addition to other known risk factors, within the Tehran Lipid and Glucose Study (TLGS). Methods In this prospective cohort study conducted within the framework of the TLGS, 6,422 individuals aged 30 and older, who had ECG data and no history of cardiovascular disease, were examined over a follow-up period with a median of 18.1 years (IQR: 1.05). Logistic regression models, adjusted for age, gender, abdominal obesity, BMI, high blood pressure, LDL cholesterol levels, fasting blood glucose, smoking status, and education level, were used to estimate the odds ratios (OR) for ECG abnormalities regarding CVD mortality. Results Overall, during the 19-year follow-up period, 233 CVD-related deaths occurred, resulting in a cumulative incidence of mortality of 3.63% in the study population. Individuals with Q-wave abnormalities (OR = 2.060, 95% CI: 1.327–3.198, P = 0.001) and T-wave abnormalities (OR = 1.990, 95% CI: 1.327–3.986, P = 0.001) had approximately twice the risk of CVD mortality compared to those without these abnormalities. However, ECG abnormalities such as ST-segment (OR = 1.169, 95% CI: 0.728–1.879, P = 0.518), QRS duration (OR = 0.780, 95% CI: 0.385–1.582, P = 0.492), and PR interval (OR = 1.406, 95% CI: 0.297–6.662, P = 0.668) did not show a significant association with CVD mortality. Conclusion Among the ECG abnormalities (ST, T, Q, PR, QRS), Q and T abnormalities are associated with CVD mortality. It can be concluded that ECG abnormalities in asymptomatic adults are related to the risk of CVD mortality and can serve as warning factors for the development of mortality from CVD.